Effect of the angle of shoulder flexion on the reach trajectory of children with spastic cerebral palsy. (January 2015) - Furuya, Makiko; Ohata, Koji; Izumi, Keisuke; Matsubayashi, Jun; Tominaga, Wataru; Mitani, Akira
Highlights: We examined the reach trajectory of children with spastic CP. The reach trajectory in children with severe CP changes with shoulder flexion angle. A large angle of shoulder flexion induces great outward deviation in the trajectory. Abstract: Many children with cerebral palsy (CP) use a wheelchair during activities of daily living and often extend their hand upward and downward to reach objects in a seated position in a wheelchair. However, the effect of shoulder position on reaching movements of children with CP is not established. The purpose of this study was to determine the effect of the angle of shoulder flexion on the reach trajectory of children with spastic CP. Seven children with mild CP [Manual Ability Classification System (MACS) levels I–II], five children with severe CP (MACS levels III–V) and six typically developing (TD) children participated. We prepared the device to have a top board with variable tilting angle in order to reduce the effect of gravity imposing on reaching movements. By using this device, the subjects could extend their arm by sliding it on the board to push a target button. The reaching movements were performed with the more affected hand at three angles (60°, 90° and 120°) of shoulder flexion and captured using a camera motion analysis system. Subjects in the TD and mild CP groups reached the target at 60°, 90° and 120° of shoulder flexion. Subjects of the severe CP group reached the target at 60° and 90° of shoulder flexion, but two of the subjects could not reach the target at 120° of shoulder flexion. The TD and mild CP groups showed smooth and almost straight trajectories at all three angles of shoulder flexion; however, the reach trajectory in the subjects with severe CP changed with the angle of shoulder flexion. A large angle of shoulder flexion induced great outward deviation in the trajectory. These findings suggest that the difficulty of the reaching task is changed depending on the shoulder joint angle in children with severe CP and that therapeutic interventions for children with severe CP should be provided in a manner appropriate for the shoulder joint angle.